Nanotechnology potential in seed priming for sustainable agriculture - Pereira, Anderson Do Espirito Santo [UNESP]; Oliveira, Halley Caixeta; Fraceto, Leonardo Fernandes [UNESP]; Santaella, Catherine (MDPI, 2021)
Our agriculture is threatened by climate change and the depletion of resources and biodiversity. A new agriculture revolution is needed in order to increase the production of crops and ensure the quality and safety of food, in a sustainable way. Nanotechnology can contribute to the sustainability of agriculture. Seed nano-priming is an efficient process that can change seed metabolism and signaling pathways, affecting not only germination and seedling establishment but also the entire plant lifecycle. Studies have shown various benefits of using seed nano-priming, such as improved plant growth and development, increased productivity, and a better nutritional quality of food. Nano-priming modulates biochemical pathways and the balance between reactive oxygen species and plant growth hormones, resulting in the promotion of stress and diseases resistance outcoming in the reduction of pesticides and fertilizers. The present review provides an overview of advances in the field, showing the challenges and possibilities concerning the use of nanotechnology in seed nano-priming, as a contribution to sustainable agricultural practices.
Keywords: Germination; Nanoparticles; Plant resistance; Seed coating; Seed nano-priming; Sustainability